Impact of Oxidative Stress and Antiepileptic Drug Treatment on Oxidative Markers in Children with Newly Diagnosed Idiopathic Epilepsy: A Comparative Study of Valproate and Oxcarbazepine - bapan, Anupam Bahe; Reddy, Vamsikrishna (Journal of Neonatal Surgery, 2025)
This study investigates the role of oxidative stress in newly diagnosed idiopathic epilepsy and the effects of antiepileptic drugs (AEDs), specifically valproate (VPA) and oxcarbazepine (OXC), on oxidative stress markers, including nitric oxide (NO), xanthine oxidase (XO), and malondialdehyde (MDA). Seventy-five children (32 girls and 43 boys, aged 5-12 years) with newly diagnosed epilepsy and 15 healthy controls were included. The patients were divided into three treatment groups: 26 treated with VPA, 26 treated with OXC, and 23 treated with other AEDs. Blood samples were collected before treatment and at 3 and 6 months after treatment to measure NO, XO, and MDA levels. At baseline, NO concentrations were significantly higher in epileptic children compared to controls (p = 0.002). No significant differences were observed in XO or MDA levels between groups at baseline (p = 0.231 and p = 0.636, respectively). After 3 months, MDA levels decreased significantly in both the VPA and OXC groups, with continued reduction at 6 months. In contrast, MDA levels remained unchanged in the control group. NO levels also decreased significantly in both VPA and OXC groups at 6 months. High XO concentrations were observed in both medication groups over the study period. In conclusion, this study highlights elevated oxidative stress in children with idiopathic epilepsy and suggests that both VPA and OXC reduce oxidative stress markers, with OXC showing a greater reduction in MDA. Further studies with larger sample sizes and placebo controls are needed to confirm the antioxidant effects of OXC in pediatric epilepsy.